IMPLEMENTASI PENDIDIKAN KARAKTER MELALUI NORMA SOSIAL UNTUK MEMBENTUK KEPRIBADIAN SISWA KELAS IV SDN KOROULON 2 NGEMPLAK SLEMAN TAHUN PELAJARAN 2023/2024 - Suryana; Tarto (Jurnal Sosialita, 2026)
In schools, character education can be carried out by instilling social norms through activities, either in the form of regulations or embedded in the learning process in the classroom. The purpose of this study is to describe the implementation of character education through social norms to shape the personality of grade IV students of SDN Koroulon 2 Ngemplak in the 2023/2024 academic year and the factors that influence it. The research approach uses a qualitative approach with the data collection methods used being interviews, observation and documentation. Data analysis was carried out using qualitative methods, namely data reduction, data presentation, and drawing conclusions. The results of the data analysis show that the implementation process of character education in grade IV at SD Negeri Koroulon 2 Ngemplak has two methods, namely learning in the classroom and outside the classroom. The process of implementing character education in grade IV at SD Negeri Koroulon 2 Ngemplak in the classroom already contains elements that indicate the integration of character education through good social norms. Meanwhile, learning outside the classroom is carried out with efforts to increase social awareness in students, in addition to being emphasized through Islamic Religion and Social Sciences subjects, also through activities determined by the school such as Class Alms Activities, Condolences and Funeral Prayers, and Environmental Cleaning Activities. Efforts made by teachers in implementing character education through social norms in class IV of Koroulon 2 Ngemplak Elementary School in the learning process are through understanding, habituation of social norms, and direction aimed at students.